摆线齿准双曲面齿轮模拟加工系统的界面设计及相关检验 - 李权才; 王星星; 付丽; 乔雪涛 (Jixie chuandong)
The interface design principle and constitution of simulation machining system of epicycloidal hypoid gears is briefly introduced.The interface content of simulation machining system of epicycloidal hypoid gear is described in detail,including interface booting,data input,gear parameters design,feasibility test,strength verification,result output,help and prompt.The solid three-dimensional model of cutter tool and gear blank can be established by the simulation machining system of epicycloidal hypoid gear,it can be used to check and analyze the cutter interference,tooth surface scratches and gear ridge grooves.A theoretical basis for optimization design and manufacture of epicycloidal hypoid gears is provided.